Electron Energization at a Reconnecting Magnetosheath Current Sheet. Issue 16 (30th August 2018) - Eriksson, Elin; Vaivads, Andris; Graham, Daniel B.; Divin, Andrey; Khotyaintsev, Yuri V.; Yordanova, Emiliya; André, Mats; Giles, Barbara L.; Pollock, Craig J.; Russell, Christopher T.; Contel, Olivier Le; Torbert, Roy B.; et al.
Abstract: We present observations of electron energization within a sub‐ion‐scale magnetosheath current sheet (CS). A number of signatures indicate ongoing reconnection, including the thickness of the CS (∼0.7 ion inertial length), nonzero normal magnetic field, Hall magnetic fields with electrons carrying the Hall currents, and electron heating. We observe localized electron acceleration and heating parallel to the magnetic field at the edges of the CS. Electrostatic waves observed in these regions have low phase velocity and small wave potentials and thus cannot provide the observed acceleration and heating. Instead, we find that the electrons are accelerated by a parallel potential within the separatrix regions. Similar acceleration has been reported based on magnetopause and magnetotail observations. Thus, despite the different plasma conditions in magnetosheath, magnetopause, and magnetotail, the acceleration mechanism and corresponding heating of electrons is similar. Plain Language Summary: Magnetic reconnection is an important physical energy conversion process in astrophysical and laboratory plasmas. The easiest place to analyze magnetic reconnection is in near‐Earth space. Due to lack of sufficient electron resolution of previous spacecraft missions, there are many unanswered questions regarding electron heating and acceleration processes at small scales. In particular, the regime where thermal pressure dominates over magnetic pressure, the most common state of plasmas in the Universe, is little explored. In this letter we study such a regime using the four‐spacecraft Magnetospheric Multiscale mission. We analyze a reconnecting current sheet in the magnetosheath. We show that electrons are energized by a parallel potential, similar to what has been observed in the different plasma regimes the magnetopause and magnetotail. Thus, despite different plasma conditions, a similar acceleration mechanism and corresponding heating of electrons is occurring in all these regions. Key Points: Sub‐ion‐scale thin reconnecting magnetosheath current sheet is investigated Electron acceleration and heating parallel to the magnetic field is observed at separatrix regions The acceleration is due to parallel acceleration potential